Gambaran Tingkat Pengetahuan, Sikap Tindakan terhadap Tablet Fe, dan Status Gizi pada Remaja Putri Anemia - ansyariah, ummarroh; Laraeni, Yuli; Utama, L. Juntra; Adiyasa, I Nyoman (Student Journal Nutrition (SJ Nutrition), 2023)
Background : Anemia is a body condition in which the level of hemoglobin in the blood is below normal or is experiencing a decrease. Based on the 2018 Riskesdas data, the prevalence of anemia in adolescents is 32%, meaning that 3-4 out of 10 adolescents suffer from anemia. The percentage of young women consuming iron tablets <52 was 98.6%, while young women consuming iron tablets > 52 was 1.4% (Ministry of Health, 2018). Research Methods: The research method used is analytic observational, with a cross-sectional research design. The sample used was 33 young women who had anemia. Research Results: Description of the level of knowledge is 10 (30.3%). Less than 13 people (39.4%) and 10 students who have a good level of knowledge (30.3%). The average attitude level is 14 (42.4%). The attitude level is less than 5 (15.2%) and 5 students have a good attitude level (15.2%). Description Action Level is being there are 9 people (27.3%). Less action rate as many as 19 students (57.6%). Good action as much as 5 students (15.2%). The nutritional status description of the sample is 27 female students who have a good nutritional status level (82%). There were 2 undernourished students (6%), 2 students who were in the overnutrition category (6%), 2 students who were in the Obesity category (6%). Conclusion: The highest level of knowledge is in the less category, 13 people with a percentage of 39%. The highest level of attitude in the medium category is 14 people with a percentage of 42.4%. and the highest level of action was in the less category, namely 57.6%, and the highest nutritional status was in the good category, namely 27 people with a percentage of 82%. Keywords: Level of Knowledge, Attitudes, Actions, Nutritional Status, Anemia, and Young Women.